Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)\(\dfrac{-6}{11}:\left(\dfrac{3}{5}.\dfrac{4}{11}\right)=\dfrac{-5}{2}\)
b)\(\dfrac{7}{12}+\dfrac{5}{12}:6-\dfrac{14}{30}=\dfrac{67}{370}\)
c)\(\left(\dfrac{4}{5}+\dfrac{1}{2}\right):\left(\dfrac{3}{13}-\dfrac{8}{13}\right)=-\dfrac{169}{50}\)
d)\(\left(\dfrac{2}{3}-\dfrac{1}{4}+\dfrac{5}{11}\right):\left(\dfrac{5}{12}+1-\dfrac{7}{11}\right)=\dfrac{115}{103}\)
\(\dfrac{1}{2}+\dfrac{3}{4}-\left(\dfrac{3}{4}-\dfrac{4}{5}\right)\)
=\(\dfrac{1}{2}+\dfrac{3}{4}-\dfrac{3}{4}+\dfrac{4}{5}\)
=\(\left(\dfrac{1}{2}+\dfrac{4}{5}\right)+\left(\dfrac{3}{4}-\dfrac{3}{4}\right)\)
=\(\left(\dfrac{5}{10}+\dfrac{8}{10}\right)+0\)
=\(\dfrac{13}{10}\)
\(-\dfrac{7}{25}.\dfrac{11}{13}+\left(-\dfrac{7}{25}\right).\dfrac{2}{13}-\dfrac{18}{25}\)
=\(-\dfrac{7}{25}.\cdot\left(\dfrac{11}{13}+\dfrac{2}{13}\right)-\dfrac{18}{25}\)
=\(-\dfrac{7}{25}.1-\dfrac{18}{25}\)
=\(-\dfrac{7}{25}-\dfrac{18}{25}\)
=\(-\dfrac{25}{25}\) = \(-1\)
2/3-6/12+1/4 = 5/12
4/12-18/24+5/2 = 25/12
-5/7*11/9+5/7*4/9 = -5/9
-3/8*13/11-3/8*3/11 = -6/11
Bài 1: Tính
1/ \(\dfrac{-2}{-5}-\left(\dfrac{-4}{3}\right)\)
\(=\dfrac{2}{5}-\left(\dfrac{-4}{3}\right)\)
\(=\dfrac{6}{15}-\left(\dfrac{-20}{15}\right)\)
\(=\dfrac{6-\left(-20\right)}{15}\)
\(=\dfrac{26}{15}\)
2/ \(\left(\dfrac{-2}{4}-\dfrac{1}{2}\right):\dfrac{2}{3}\)
\(=\left(\dfrac{-2}{4}-\dfrac{2}{4}\right):\dfrac{2}{3}\)
\(=-1:\dfrac{2}{3}\)
\(=-1.\dfrac{3}{2}\)
\(=\dfrac{-3}{2}\)
3/ \(\dfrac{5}{12}.\dfrac{17}{11}-\dfrac{5}{12}.\dfrac{7}{11}+\dfrac{5}{12}.\dfrac{1}{11}\)
\(=\dfrac{5}{12}.\left(\dfrac{17}{11}-\dfrac{7}{11}+\dfrac{1}{11}\right)\)
\(=\dfrac{5}{12}.\left(\dfrac{17-7+1}{11}\right)\)
\(=\dfrac{5}{12}.1\)
\(=\dfrac{5}{12}\)
Bài làm
1.
11 3/13 - ( 2 4/7 + 5 3/13 )
= 11 3/13 - 2 4/7 - 5 3/13
= ( 11 3/13 - 5 3/13 ) - 2 4/7
= { (11 - 5 ) . ( 3/13 - 3/13 ) } - 2 4/7
= ( 6 . 0 ) - 2 4/7
= 0 - 2 4/7
= 2 4/7
= 18/7
2 .
19 5/8 : 7/12 + ( -15 1/4) : 7/12
= { 19 5/8 + ( -15 1/4 ) } : 7/12
= [ { 19 + ( - 15) } . ( 5/8 + 1/4 ) ] : 7/12
= { 4 . ( 5/8 + 2/8 ) } : 7/12
= ( 4 . 7/8 ) : 7/12
= 1.7/2 : 7/12
= 7/2 : 7/12
= 7/2 . 12/7
= 1.1/6.1
= 1/6
3 .
2/5 . 1/3 - 2 2/15 : 1/5 + 3/5 . 1/3
= 1/3 . ( 2/5 + 3/5 ) - 2 2/15 : 1/5
= 1/3 . 5/5 - 32/15 . 5/1
= 1/3 . 1 - 32.1/3.1
= 1/3 - 32/3
= -31/3
4 .
( 3 1/3 + 2,5 ) : ( 3 1/6 - 4 1/5 ) - 11/31
= ( 10/3 + 25/10 ) : { ( 3 - 4 ) . ( 1/6 - 1/5 ) - 11/31
= ( 10/3 + 5/2 ) : { (-1) . ( 5/30 - 6/30 ) } - 11/31
= ( 20/6 + 15/6 ) : { (-1) . (-1)/30 } - 11/31
= 35/6 : 1/30 - 11/31
= 35/6 . 30/1 - 11/31
= 35.5/1.1 - 11/31
= 175 - 11/31
= 5425/31 - 11/31
= 5414/31
5.
75% - 1 1/5 + 0,5 : 5/12 - (-1/2)2
= 75/100 - 6/5 + 5/12 - 1/4
= 3/4 - 6/5 + 5/12 - 1/4
= ( 3/4 - 1/4 ) + ( 5/12 - 6/5 )
= 2/4 + ( 25/60 - 30/60 )
= 1/2 + (-5)/60
= 1/2 + (-1)/12
= 6/12 + (-1)/12
= 5/12
Đúng thì k cho mình nha !
1)
11 3/13 - ( 2 4/7 + 5 3/13 )
= 11 3/13 - 2 4/7 - 5 3/13
= ( 11 3/13 - 5 3/13 ) - 2 4/7
= { (11 - 5 ) . ( 3/13 - 3/13 ) } - 2 4/7
= ( 6 . 0 ) - 2 4/7
= 0 - 2 4/7
= 2 4/7
= 18/7
2 )
19 5/8 : 7/12 + ( -15 1/4) : 7/12
= { 19 5/8 + ( -15 1/4 ) } : 7/12
= [ { 19 + ( - 15) } . ( 5/8 + 1/4 ) ] : 7/12
= { 4 . ( 5/8 + 2/8 ) } : 7/12
= ( 4 . 7/8 ) : 7/12
= 1.7/2 : 7/12
= 7/2 : 7/12
= 7/2 . 12/7
= 1.1/6.1
= 1/6
3 )
2/5 . 1/3 - 2 2/15 : 1/5 + 3/5 . 1/3
= 1/3 . ( 2/5 + 3/5 ) - 2 2/15 : 1/5
= 1/3 . 5/5 - 32/15 . 5/1
= 1/3 . 1 - 32.1/3.1
= 1/3 - 32/3
= -31/3
4 )
( 3 1/3 + 2,5 ) : ( 3 1/6 - 4 1/5 ) - 11/31
= ( 10/3 + 25/10 ) : { ( 3 - 4 ) . ( 1/6 - 1/5 ) - 11/31
= ( 10/3 + 5/2 ) : { (-1) . ( 5/30 - 6/30 ) } - 11/31
= ( 20/6 + 15/6 ) : { (-1) . (-1)/30 } - 11/31
= 35/6 : 1/30 - 11/31
= 35/6 . 30/1 - 11/31
= 35.5/1.1 - 11/31
= 175 - 11/31
= 5425/31 - 11/31
= 5414/31
5)
75% - 1 1/5 + 0,5 : 5/12 - (-1/2)2
= 75/100 - 6/5 + 5/12 - 1/4
= 3/4 - 6/5 + 5/12 - 1/4
= ( 3/4 - 1/4 ) + ( 5/12 - 6/5 )
= 2/4 + ( 25/60 - 30/60 )
= 1/2 + (-5)/60
= 1/2 + (-1)/12
= 6/12 + (-1)/12
= 5/12
BÀI 1
a, \(5\times\frac{-7}{10}=\frac{-35}{10}=\frac{-7}{2}\)
b, \(\frac{4}{5}\times\frac{-7}{10}=\frac{-28}{50}=\frac{-14}{25}\)
c, \(\frac{4}{9}+\frac{4}{3}\times\frac{16}{4}=\frac{4}{9}+\frac{16}{3}=\frac{52}{9}\)
d, \(\frac{11}{22}-\frac{3}{9}\times\frac{14}{21}=\frac{11}{22}-\frac{2}{9}=\frac{55}{198}=\frac{5}{18}\)
BÀI 2
\(A=\frac{6}{13}\times\frac{5}{7}+\frac{6}{13}\times\frac{2}{7}+\frac{17}{13}\)
\(A=\frac{30}{91}+\frac{12}{91}+\frac{17}{13}\)
\(A=\frac{30}{91}+\frac{12}{91}+\frac{119}{91}\)
\(A=\frac{161}{91}=\frac{23}{13}\)
\(B=\frac{11}{15}\times\frac{4}{11}+\frac{11}{15}\times\frac{5}{11}+\frac{11}{15}\times\frac{2}{11}\)
\(B=\frac{4}{15}+\frac{1}{3}+\frac{2}{15}\)
\(B=\frac{11}{15}\)
\(C=\left(\frac{19}{64}-\frac{33}{22}+\frac{24}{51}\right)\times\left(\frac{1}{5}-\frac{1}{15}-\frac{2}{15}\right)\)
\(C=\frac{-797}{1088}\times0\)
\(C=0\)
\(D=\frac{8}{13}\times\frac{7}{12}+\frac{8}{13}\times\frac{5}{12}-\frac{1}{12}\)
\(D=\frac{14}{39}+\frac{10}{39}-\frac{1}{12}\)
\(D=\frac{83}{156}\)
bạn biết câu náy không (24 + 11) . {546 - [14 . (64 - 2^{3}3) : 2]} =
\(=\dfrac{88-33+60}{132}:\dfrac{55+132-84}{132}\)
\(=\dfrac{115}{103}\)